Information Systems Success and Management Control Effectiveness in MSMEs: The Roles of System Use and User Satisfaction - Muhammad Evan Hakim; Moh Yudi (Management Analysis Journal, 2026)
This study examines how Information Quality (IQ) and Service Quality (SQ) influence Management Control Effectiveness (MCE) in Micro, Small, and Medium Enterprises (MSMEs) in Cirebon City, by considering System Use (SU) as a mediating variable and User Satisfaction (US) as a moderating variable. Drawing on the DeLone and McLean IS Success Model, this study addresses the limited empirical evidence on how accounting information systems support management control practices in MSMEs. Data were collected from 180 MSME actors who use accounting information systems and analysed using Partial Least Squares–Structural Equation Modelling (PLS-SEM). The findings show that SU plays a central role in improving MCE and mediates the relationship between SQ and MCE. IQ has a direct positive effect on MCE, while its relationship with SU is moderated by US. User satisfaction also strengthens the role of service quality in encouraging system use. These findings highlight that the effectiveness of management control in MSMEs depends not only on the quality of information and services, but also on how actively users engage with the system. The study suggests that improving digital literacy and user-oriented system support can enhance the benefits of accounting information systems for MSME management control.